Introduction au dossier Bordage - Claire Cornillon; Natacha Vas-Deyres (ReS Futurae)
This introduction to the issue about the french writer Pierre Bordage presents its carreer in genres such as science fiction and fantasy and the specificities of its work. This issue aims at exploring novels and short stories that were for the moment less studied or proposing new approaches, such as transmedia or linguistics, in order to add to the already existing research on this author.